Medicinal use of cannabis in the treatment of epilepsy (Research, Society and Development, 2022)
Epilepsy is a neurological disease, characterized by excessive neuronal activity, the seizures. Studies show that the incidence of symptoms is higher in the first year of life, and the approximate number of patients affected in the world is 70 million people. Objective: The objective of this present work is to investigate the medicinal use of cannabis, as well as to analyze its safety and efficacy in the treatment of epilepsy. Methodology: To make this possible, a systematic review was carried out in such databases: ScienceDirect, Virtual Health Library – VHL and Pubmed, using the descriptors cannabis and epilepsy, cannabis and pharmacology, cannabis treatment, epilepsy. Results: Drugs that are used as a form of treatment are effective in about 70% of cases, with the remaining 30% presenting a refractory form to treatment. These circumstances generate fervor in the development of effective therapeutic solutions in the treatment of these refractory cases, in this way, cannabis comes to gain space, when it has several therapeutic functions, such as reducing the frequency of seizures, which is of great value for such patients. Conclusion: From the data collection, the conclusion is that the use of cannabis has a promising effect in the treatment of epilepsy, when compared to conventional pharmacotherapy, even with some side effects that are somewhat acceptable. It is of considerable importance to emphasize that because it is an extract that originates from a plant seen as a psychoactive drug, its label becomes valuable for scientific advancement, requiring further analysis and future studies.